MAXILLOFACIAL PROSTHESIS USING NYLON THERMOPLASTIC WITH HOllOW BULB IN CASE OF CLASS III ARAMANY IN PATIENTS WITH PALATO SCISIS HEREDITERY - , Azhindra ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Background: patients with palato scisis (cleft palate) caused by hereditary or congenital defect will be causing speech disorders (nasal), swallowing, and masticating, also aesthetical and psychological problems. Purpose: to inform how to rehabilitate defects on face with a maxillofacial prosthesis nylon thermoplastic with hollow bulb which is useful to restore the function of speech, swallowing, masticating, aesthetical and psychological problems of the patients. Caseand handling:46 years old male patient who came to RSGM Prof. Soedomoupon referralfrom the dental care unit of Dr.Sardjito's Hospital. When patient came, He feel that he is getting speech disorder, chewing and swallowing problems due to the presence of cleft palate which is opened and also caused by a congenital abnormality which is accompanied by loss of many teeth, especially in posterior teeth of the maxilla and he want the doctor to make him a denture. Obturator is immediately made by doctor with considering the closure of cleft palate, using a lighter material (hollow bulb material) in order to obtain the maximum retention time and restore masticating, talking capability, swallowing, aesthetical and psychologicalproblems of the patients which is designed to have high precision of retention, stabilization and occlusion which is hoped that it can restore the face of patient back to normal. Hollow bulb is a cavity which is created in maxillofacialprosthesis to cover Mouth and nasal cavity, also other defects. While insertion was being examined on retention, stabilization, occlusion, aesthetic and pronunciation. Control was performed 1 week and 1 month after application. The results of the examination and evaluation after 1 week and 1 month usage of hollow bulb maxillofacialprosthesis, it is known that stabilization, occlusion and pronunciation of the patient become better. Conclusion: after using Maxillofacialprosthesis nylon thermoplastic with hollow bulb, patients with palato scisis, can speak and chew normally. Hollow bulb maxillofacial prosthesis nylon thermoplastic can also restore the maximum aesthetic, especially in the loss of anterior teeth with retention or grip as strong as gingiva so the patient can increase self confidence and restore psychological condition of patient which has been declining for such a longtime.